Utang na loob the ilonggo experience. - Baldo, Jezzebelle T.; Quirante, Rachel Joy A. (2011.)
This study aimed to investigate the construct utang na loob from the Ilonggo perspectively and to distinguish the Filipino concept of utang na loob from Trivers' model of reciprocal altruism. This research is an exploratory study which made use of focus group discussion for data collection. This data was analyzed using category pattern analysis. Based on the results, utang na loob in the Ilonggo perspective is utang na kabalaslan. Its process is parallel but not equivalent to utang na loob in the Kapwa perspective and partly in reciprocal altruism. However the differences lie in the concept, construct, dimension and repayment. Also, utang na loob in Kapwa differs with reciprocal altruism in terms of reason for helping, repayment and extent of the process.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Utang na Loob